Subcloning of cytochrome P450 2C19 (CYP2CL9) In escherichia coli strain BL21 - Abdullah, Nur Azieyati (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2011)
Drug metabolism or biotransformation of drug undergo molecular alteration in which, it converts nonpolar, lipohilic pharmacologically active drug molecules into polar, inactive, or nontoxic metabolites in the body before excretion. In human, the cytochrome P450 (CYP) enzymes are the major catalysts involved in the metabolism of drugs and other xenobiotics that enter the body. The CYP2C19 enzyme is responsible for the metabolism of several important drugs such as antidepressants. This study was conducted to generate CYP2C19 enzyme recombinant for pharmocogenomics study. Constructed eDNA of CYP2C19 was purchased from Origene, USA. The cloning process was performed by using RapidShuttling™ Kit (Origene, USA). The CYP2Cl9 gene from TrueORF Entry Vector was transferred into an expression vector, pEX-CHis. The desire plasmid was extracted using commercial QIAprep Spin Miniprep Kit (Qiagen, Germany) and DNA sequence of CYP2C19 was confirmed by DNA sequencing using ABI PRISMA ™ 3130x/ Genetyx Analyzer. The size of PCR product was shown at -1.5kb on agarose gel. Desire DNA sequence of CYP2C 19 enzyme shown same sequence as in Gene bank. As a conclusion, CYP2CJ9 gene was successfully cloned. The combination of molecular biology and relative exposure to CYP2C19 substrates and genetic testing eventually lead to a better appreciation to avoid toxicological outcomes that may currently result from this enzyme and variations in its expression.